Survey of Views of Medical Students on Telemedicine Methods Developed in the Mazandaran University of Medical Sciences Iran - Ahad Alizadeh; Akbar Mohammadi; Mohammad Khademloo; Hadi Hosaini (Kerman University of Medical Sciences, 2013)
Background & Objective: Telemedicine is the use of new communication and information technologies to provide clinical services health care and transferring of information for care of patients from a geographical distance The aim of this research was to determine the views of medical students on the development of telemedicine procedures in the Mazandaran University of Medical Sciences Iran Methods: A sample of 90 medical students was selected randomly in the first semester of study of 201112 The students views were assessed using a questionnaire of 33 questions consisting of three parts: demographic data questions in five areas (organizational factors technological factors stakeholders agents information literacy and environmental factors) and student use of the various areas of technology (computers internet medical websites medical applications and etc) Results: In the questions concerning the scope of the organizational factors 655% of students had a positive opinion in regard to admission to the structural changes in the organization Among the factors of technology 867% of students had positive views on broadband access in the factors of stakeholders 589% on empowering the private sector in implementing telemedicine in the information literacy 755% on students skills in using computers and the Internet and in the environmental factors 800% on economic factors for the plan Conclusion: Students believed the role of economic factors (cost appropriate technology and etc) to be more important than cultural factors (physicianpatient interaction culture community support willingness of the family and etcetera)